A high thermal conductivity multi-resin powder mica tape and preparation method thereof
By using liquid epoxy resin and curing agent in high-thermal conduction multi-glue powder mica tape to enhance the thermal conductivity of the adhesive, and combining a small amount of inorganic thermal conduction powder, the electrical life and the electrical life of the thermal conduction powder in the prior art are solved. The problem of decreasing breakdown field strength has achieved the effect of high thermal conductivity and low filler usage, reduced manufacturing costs and met the application requirements of high-voltage motor main insulation.
Patent Information
- Application Number
- CN202211116474.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-14
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-09-14
AI Technical Summary
The existing high-thermal conductivity multi-glue powder mica belts need to be added with too much inorganic thermal conductivity, resulting in a decrease in the electrical life and breakdown field strength of the main insulation, which cannot effectively improve the thermal conductivity and increase manufacturing cost.
Use liquid epoxy resin and curing agent as raw materials to enhance the thermal conductivity of the adhesive, and reduce interface defects through the combination of a small amount of inorganic thermal conduction powder, and design a high-thermal conduction multi-glue powder mica belt to reduce the use of thermal conduction powder. , improve the thermal conductivity while maintaining electrical life and breakdown field strength.
Under the premise of increasing the same thermal conductivity coefficient, it is achieved to significantly reduce the amount of thermally conductive powder addition, reduce interface defects, improve the electrical life and breakdown field strength of the main insulation, reduce manufacturing costs, and meet the application requirements of high-voltage motor main insulation.
Smart Images

Figure DEST_PATH_IMAGE002
Abstract
Description
Technical Field
[0001] The invention relates to the field of manufacturing an insulation system of a high-voltage motor and related materials thereof, and more specifically, to a high-thermal-conductivity multi-resin powder mica tape used for manufacturing main insulation of a high-voltage motor. Background Art
[0002] Since air-cooled high-voltage motors do not require auxiliary machines such as water treatment or hydrogen production and their control equipment, they have the advantages of simple structure, low cost, simple repair and maintenance, high operational reliability, and rapid start-up. Therefore, they are widely used in power grid peak-shaving motors, pumped storage motors, mining motors, high-power drive motors, etc., and have developed rapidly in the past decade.
[0003] However, since the heat generated by the stator coil or wire rod when the air-cooled motor is running must first pass through the main insulation (insulation to the ground) before it can be transferred to the outside of the coil or wire rod and the iron core, and then taken away by the air cooling system, the smaller the thermal resistance of the main insulation, the higher the cooling efficiency of the motor, the lower the temperature rise of the coil or wire rod, the smaller the loss of the motor and the higher the reliability; or the size of the motor can be reduced at the same capacity, reducing the manufacturing cost. Therefore, reducing the thermal resistance of the main insulation has important economic and technical significance in the field of high-voltage motor manufacturing.
[0004] There are usually two ways to reduce the thermal resistance of main insulation in engineering: one is to reduce the thickness of the main insulation; the other is to increase the thermal conductivity of related insulation materials. Since the thickness of the main insulation depends on many factors such as the working voltage of the motor, the insulation level of the insulation material, the insulation structure design and the manufacturing level of the coil or wire rod, it is usually determined by the electrical life of the coil or wire rod, the actual operating conditions and reliability requirements. Therefore, before a major breakthrough in the insulation level is achieved, the thickness of the main insulation cannot usually be reduced. According to current technical conditions, a more reliable method is to reduce the thermal resistance of the main insulation by increasing the thermal conductivity of related insulation materials.
[0005] In order to improve the thermal conductivity of the main insulation material, a lot of improvement research has been carried out on the materials used to manufacture the main insulation at home and abroad in the past thirty years. So far, the improvement methods currently adopted are basically to improve the thermal conductivity of the main insulation by adding inorganic thermal conductive powder to the mica tape used to prepare the main insulation. This "powder-filled" high thermal conductivity mica tape has a technical difficulty that is difficult to overcome at this stage: since the thermal conductivity of the existing high thermal conductivity multi-glue powder mica tape is strongly dependent on the amount of inorganic thermal conductive powder added, a large amount of inorganic powder (greater than 60g / ㎡) must be added to obtain a higher thermal conductivity. However, the existing technology cannot completely eliminate the defects on the interface between the organic adhesive and the inorganic thermal conductive powder. The more powder is added, the more interface defects there are. This defect will cause the accumulation of space charge, the distortion and local concentration of the electric field, thereby increasing the partial discharge of the main insulation, reducing the electrical life, breakdown field strength and reliability of the main insulation, resulting in the fact that the high thermal conductivity multi-glue powder mica tape has not yet been put into practical use. Summary of the invention
[0006] The cooling method and heat dissipation technology of high-voltage motors are very important links in the design and manufacturing technology of high-voltage motors, which directly affect various economic and technical indicators, manufacturing costs and operating reliability of high-voltage motors. The present invention solves the technical problem that the high thermal conductivity multi-powder mica tape in the prior art needs to add too much thermal conductive powder, which causes the electrical life and breakdown field strength of the main insulation to drop too much. The present invention provides a high thermal conductivity multi-powder mica tape, which can achieve the same improvement in thermal conductivity with a lower amount of thermal conductive powder added (not more than 35g / ㎡). A new formula is introduced into the adhesive of the high thermal conductivity multi-powder mica tape of the present invention, which enhances the thermal conduction of the adhesive itself. Combined with the thermal conductive powder, the amount of inorganic thermal conductive powder added can be greatly reduced under the premise of the same thermal conductivity improvement, and the defects on the interface between the organic adhesive and the inorganic thermal conductive powder are reduced, and the adverse effects of excessive addition of thermal conductive powder on the dielectric properties of the main insulation are reduced, so that it can maintain the electrical life and breakdown field strength of the main insulation while improving the thermal conductivity, so as to meet the application requirements of the high thermal conductivity multi-powder mica tape for the main insulation of the high-voltage motor.
[0007] The present invention adopts the following technical solution:
[0008] A high thermal conductivity multi-glue powder mica tape, which is composited by powder mica paper, alkali-free glass cloth, adhesive and inorganic thermal conductive powder, wherein the mass per unit area of each component material is: powder mica paper 60-130g / ㎡, alkali-free glass cloth 16-45g / ㎡, adhesive 50-105g / ㎡, inorganic thermal conductive powder 20-50g / ㎡; the raw materials for preparing the adhesive include liquid epoxy resin and curing agent. Preferably, the powder mica paper is 60-90g / ㎡, the alkali-free glass cloth is 25-45g / ㎡, the adhesive is 60-90g / ㎡, and the inorganic thermal conductive powder is 20-40g / ㎡.
[0009] In the present invention, the liquid epoxy resin is one or more of phenolic epoxy resin, resorcinol diglycidyl ether, bisphenol A type liquid epoxy resin, and bisphenol F type liquid epoxy resin.
[0010] In the present invention, the powdered mica paper is an existing product, which is made of natural muscovite; in the high thermal conductivity multi-resin powdered mica tape, the powdered mica paper is a layer.
[0011] In the high thermal conductivity multi-resin powder mica tape of the present invention, the alkali-free glass cloth is one or two layers; when the alkali-free glass cloth is two layers, the powder mica paper is located between the two layers of alkali-free glass cloth; the mass per unit area refers to the mass per unit area of all alkali-free glass cloths.
[0012] In the present invention, the curing agent is one or more of 4,4′-dihydroxybiphenyl, 4,4′-diaminobiphenyl, 4,4′-dicarboxylic acid biphenyl, 4,4′-dicarboxylic acid p-terphenyl, 4,4′-dihydroxy p-terphenyl, resorcinol formaldehyde resin, and hydroquinone formaldehyde resin.
[0013] In the present invention, the inorganic thermally conductive powder is one or two of BN and Al2O3; the median particle size of the inorganic thermally conductive powder is 0.1 to 30 μm.
[0014] The present invention uses liquid epoxy resin and curing agent as raw materials, reacts in a solvent to obtain an adhesive, which plays the role of bonding mica paper and alkali-free glass cloth. The solvent is a conventional organic solvent, which is used to dissolve the curing agent and serves as a dispersant for the reaction system. Preferably, the reaction conditions are reflux reaction at 105-110°C for 3-5 hours.
[0015] The high thermal conductivity multi-resin powder mica tape of the present invention is mainly used for preparing the main insulation of high-voltage motors. The production process of the high thermal conductivity multi-resin powder mica tape of the present invention is consistent with that of ordinary high thermal conductivity multi-resin powder mica tape, for example: preparation of adhesive, mixing of adhesive and thermal conductive powder, gluing of glass cloth, compounding of gluing glass cloth and mica paper, drying, rolling and slitting of mica tape and the like.
[0016] Compared with the prior art, the present invention has the following advantages:
[0017] (1) The present invention uses liquid epoxy resin and curing agent as raw materials, which enhances the transmission of phonons in the adhesive and improves the thermal conductivity of the adhesive itself. Compared with the prior art using epoxy curing systems such as tung oil anhydride and tung maleic anhydride, the thermal conductivity of the adhesive of the present invention is increased by 50% or more compared with the thermal conductivity of the adhesive used in the prior art of 0.17 to 0.19 W / (m·K).
[0018] (2) Since the thermal conductivity of the adhesive used in the present invention is significantly improved compared with the prior art, the adhesive is a continuous phase in the main insulation of the high-voltage motor. Combined with the effect of a small amount of thermally conductive powder, the technical effect of high thermal conductivity and low filler dosage can be achieved, and the interface defects between the adhesive and the inorganic thermally conductive powder can be reduced. Since the amount of expensive thermally conductive powder is reduced, the manufacturing cost of the high thermal conductivity multi-glue powder mica tape is also reduced.
[0019] (3) The thermal conductivity of the high-voltage motor main insulation prepared by the high thermal conductivity multi-resin powder mica tape of the present invention can reach 0.40-0.55 W / (m·K), which is 50-100% higher than the thermal conductivity of the ordinary powder-free high-voltage motor main insulation of the prior art of 0.25-0.28 W / (m·K). The breakdown field strength and electrical life are at the same level as those of the ordinary powder-free high-voltage motor main insulation of the prior art. DETAILED DESCRIPTION
[0020] The present invention uses liquid epoxy resin and curing agent as raw materials, reacts in a solvent to obtain an adhesive, and combines it with a small amount of thermally conductive powder as a bonding material for mica tape, unexpectedly achieving the technical effect of high thermal conductivity and low filler dosage. Only less than half of the filler dosage is used to achieve the technical effect of high filler in the prior art, while significantly improving the thermal conductivity while maintaining the breakdown field strength and electrical life without decreasing, solving the technical defect of the prior art that the breakdown field strength and electrical life are greatly reduced due to the high filler dosage, and correcting the technical prejudice of the prior art that high filling fillers are required to improve thermal conductivity.
[0021] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail in combination with the following embodiments and comparative examples. The embodiments described herein are only used to explain the present invention and are not used to limit the present invention. The raw materials of the present invention are all commercially available products, which meet the use requirements of mica tapes. The specifications of the powdered mica paper, alkali-free glass cloth and thermal conductive filler used in the embodiments and comparative examples are consistent. The specific preparation operation of the present invention is a conventional technology, and the production process of the high thermal conductivity multi-resin powder mica tape of the present invention is consistent with the existing high thermal conductivity multi-resin powder mica tape. The specific process steps and process parameters of the hot pressing process used to make the simulated wire rod specimens are prior art, such as: the size requirements of the simulated aluminum or copper bars, the number of wrapping layers, the wrapping tension, the pre-baking conditions, the vacuum devolatilization, the mold pressurization, the temperature rise curing, the cooling and demolding, and other process details are well known to the industry, and the embodiments will not be repeated.
[0022] The thermal conductivity of the simulated wire rod main insulation is tested in accordance with the provisions of "GB / T 29313-2012 Test method for thermal conductivity of electrical insulation materials", the breakdown field strength is tested in accordance with Section 5.5 of "JB / T 12685-2016 Technical conditions for high-voltage motor stator coils", and the electrical life is tested in accordance with Section 5.8.2 of "JB / T 12685-2016 Technical conditions for high-voltage motor stator coils".
[0023] Example 1
[0024] The high thermal conductivity multi-glue powder mica tape prepared in this embodiment contains a layer of powdered mica paper, a layer of glass cloth, an adhesive and BN thermal conductive powder, wherein the mass per unit area of each component material is: powdered mica paper 105g / ㎡, alkali-free glass cloth 20g / ㎡, adhesive 80g / ㎡, BN thermal conductive powder 30g / ㎡, the total mass per unit area is 235g / ㎡, and the thickness of the mica tape is 0.16±0.02mm.
[0025] The preparation steps of this embodiment are as follows:
[0026] (1) Adhesive preparation
[0027] 100kg of bisphenol A liquid epoxy resin with an epoxy value of 0.52mol / 100g, 40kg of 4,4′-dihydroxybiphenyl and 20kg of acetone were put into a reactor, and stirring was started. The temperature was raised to 100°C and refluxed for 4 hours. After stopping the heating, 30kg of toluene and 10kg of acetone were added in sequence. The temperature was continued to be stirred and cooled naturally. The material was discharged, filtered and barreled to obtain an adhesive with a solid content of 70%.
[0028] (2) Thermally conductive powder and adhesive composite
[0029] 100 kg of the adhesive with a solid content of 70% obtained in step (1) is put into a stirring and dispersing tank, and after starting stirring, 26.25 kg of BN thermal conductive powder with a median particle size of 20 μm is added and stirred for 2 hours to obtain an adhesive containing thermal conductive powder.
[0030] (3) Gluing of glass cloth
[0031] The adhesive containing the thermally conductive powder obtained in step (2) is transferred to the glue tank of the mica tape gluing machine equipped with a stirring device, and a given amount of 20g / ㎡ of alkali-free glass cloth is glued. By adjusting the solid content of the adhesive, the speed of the mica tape machine and the rotation speed of the gluing roller, the amount of glue applied is controlled to meet the requirements. The method for controlling and adjusting the amount of glue applied is well known to the industry and will not be repeated here.
[0032] (4) Lamination, drying, winding and slitting
[0033] The glass cloth coated with glue in step (3) is compounded with powdered mica paper with a basis weight of 105 g / m2, and then put into a drying oven for drying: the temperature of the front section of the drying oven is controlled at 70-80°C, the temperature of the middle section is controlled at 110-120°C, the temperature of the rear section is controlled at 80-90°C, and the speed is controlled at 1.5-2 m / min. After winding and slitting, a high thermal conductivity multi-glue powdered mica tape is obtained.
[0034] A high thermal conductivity multi-resin powder mica tape was used and a simulated wire rod sample with a single-side insulation thickness of 3.5 mm was made by hot pressing process. According to the test methods specified in relevant national or industrial standards, the thermal conductivity of the main insulation was measured to be 0.45 W / (m·K), the breakdown field strength was 34 kV / mm, and the electrical life was 1320 hours under a field strength of 10 kV / mm.
[0035] Example 2
[0036] The high thermal conductivity multi-glue powder mica tape prepared in this embodiment contains a layer of powdered mica paper, two layers of glass cloth, an adhesive and BN thermal conductive powder, wherein the mass per unit area of each component material is: 85 g / ㎡ of powdered mica paper, 40 g / ㎡ of two layers of alkali-free glass cloth, 80 g / ㎡ of adhesive for improving intrinsic thermal conductivity, and 30 g / ㎡ of BN thermal conductive powder. The total mass per unit area is 235 g / ㎡, and the thickness of the mica tape is 0.16±0.02 mm.
[0037] The preparation steps of this embodiment are as follows:
[0038] (1) Gluing glass cloth
[0039] The adhesive containing the thermally conductive powder obtained in step (2) of Example 1 was poured into the upper and lower glue tanks of the mica tape machine, both of which were equipped with stirring devices, and the upper and lower layers of alkali-free glass cloth with a quantitative amount of 20 g / m2 were respectively glued. By adjusting the solid content of the adhesive, the speed of the mica tape machine and the rotation speed of the glue roller, the glue amount was controlled to meet the requirements.
[0040] (2) Lamination, drying, winding and slitting
[0041] The glass cloth glued in step (1) is compounded with powdered mica paper with a basis weight of 85 g / m2, and then put into a drying oven for drying: the temperature of the front section of the drying oven is controlled at 70-80°C, the temperature of the middle section is controlled at 110-120°C, the temperature of the rear section is controlled at 80-90°C, and the speed is controlled at 1.5-2 m / min. After winding and slitting, a high thermal conductivity multi-glue powdered mica tape is obtained.
[0042] A high thermal conductivity multi-resin powder mica tape was used to manufacture a simulated wire rod sample with a single-side insulation thickness of 3.5 mm using a hot pressing process. According to the test methods specified in relevant national or industry standards, the thermal conductivity of the main insulation was measured to be 0.43 W / (m·K), the breakdown field strength was 32 kV / mm, and the electrical life under a field strength of 10 kV / mm was 1290 hours.
[0043] Example 3
[0044] The high thermal conductivity multi-glue powder mica tape prepared in this embodiment contains a layer of powdered mica paper, a layer of glass cloth, an adhesive for improving intrinsic thermal conductivity, BN thermal conductive powder and Al2O3 thermal conductive powder, wherein the mass per unit area of each component material is: powdered mica paper 105g / ㎡, alkali-free glass cloth 20g / ㎡, adhesive 85g / ㎡, BN thermal conductive powder 31g / ㎡, Al2O3 thermal conductive powder 4g / ㎡, the total mass per unit area is 245g / ㎡, and the thickness of the mica tape is 0.17±0.02mm.
[0045] The preparation steps of this embodiment are as follows:
[0046] (1) Adhesive preparation
[0047] 100 kg of resorcinol diglycidyl ether, 30 kg of 4,4′-dicarboxylic acid biphenyl and 20 kg of dimethyl sulfoxide were put into a reactor, stirring was started, the temperature was raised to 105°C and the reaction was carried out for 4 hours, and then 10 kg of resorcinol formaldehyde resin was added and stirred for 1 hour, then heating was stopped, 20 kg of toluene and 20 kg of acetone were added, stirring was continued, the temperature was naturally lowered, the material was discharged, filtered and barreled, and an adhesive with a solid content of 70% was obtained.
[0048] (2) Thermally conductive powder and adhesive composite
[0049] 100 kg of the adhesive with a solid content of 70% obtained in step (1) is put into a stirring and dispersing tank. After starting stirring, 25.5 kg of BN thermal conductive powder with a median particle size of 20 μm and 3.3 kg of Al2O3 thermal conductive powder with a median particle size of 5 μm are added. Stir for 2 hours to obtain an adhesive containing thermal conductive powder.
[0050] (3) Gluing of glass cloth
[0051] The adhesive containing the thermally conductive powder obtained in step (2) is transferred to the glue tank of the mica tape gluing machine equipped with a stirring device, and a given amount of 20g / ㎡ of alkali-free glass cloth is glued. By adjusting the solid content of the adhesive, the speed of the mica tape machine and the rotation speed of the gluing roller, the glue amount is controlled to meet the requirements.
[0052] (4) Lamination, drying, winding and slitting
[0053] The glass cloth glued in step (3) is compounded with mica paper with a basis weight of 105 g / m2, and then put into a drying oven for drying: the temperature of the front section of the drying oven is controlled at 60-70°C, the temperature of the middle section is controlled at 120-130°C, the temperature of the rear section is controlled at 90-100°C, and the speed is controlled at 1.0-1.5 m / min. After winding and slitting, a high thermal conductivity multi-glue mica tape is obtained.
[0054] A high thermal conductivity multi-resin powder mica tape was used to manufacture a simulated wire rod sample with a single-side insulation thickness of 3.5 mm using a hot pressing process. According to the test methods specified in relevant national or industry standards, the thermal conductivity of the main insulation was measured to be 0.51 W / (m·K), the breakdown field strength was 33 kV / mm, and the electrical life under a field strength of 10 kV / mm was 1300 hours.
[0055] Example 4
[0056] The high thermal conductivity multi-glue powder mica tape prepared in this embodiment contains a layer of powdered mica paper, two layers of glass cloth, an adhesive, BN thermal conductive powder and Al2O3 thermal conductive powder, wherein the mass per unit area of each component material is: 85 g / ㎡ of powdered mica paper, 40 g / ㎡ of two layers of alkali-free glass cloth, 85 g / ㎡ of adhesive for improving intrinsic thermal conductivity, 31 g / ㎡ of BN thermal conductive powder, and 4 g / ㎡ of Al2O3 thermal conductive powder. The total mass per unit area is 245 g / ㎡, and the thickness of the mica tape is 0.17±0.02 mm.
[0057] The preparation steps of this embodiment are as follows:
[0058] (1) Gluing glass cloth
[0059] The adhesive containing thermally conductive powder obtained in step (2) of Example 3 is poured into the upper and lower glue tanks of the mica tape machine, both of which are equipped with stirring devices, and glue is applied to the upper and lower layers of alkali-free glass cloth with a quantitative amount of 20g / ㎡ respectively. By adjusting the speed of the mica tape machine and the rotation speed of the glue roller, the glue amount is controlled to meet the requirements.
[0060] (2) Lamination, drying, winding and slitting
[0061] The glass cloth glued in step (1) is compounded with powdered mica paper with a basis weight of 85 g / m2, and then put into a drying oven for drying: the temperature of the front section of the drying oven is controlled at 60-70°C, the temperature of the middle section is controlled at 120-130°C, the temperature of the rear section is controlled at 90-100°C, and the speed is controlled at 1.0-1.5 m / min. After winding and slitting, a high thermal conductivity multi-glue powdered mica tape is obtained.
[0062] A high thermal conductivity multi-resin powder mica tape was used to manufacture a simulated wire rod sample with a single-side insulation thickness of 3.5 mm using a hot pressing process. According to the test methods specified in relevant national or industry standards, the thermal conductivity of the main insulation was measured to be 0.48 W / (m·K), the breakdown field strength was 31 kV / mm, and the electrical life under a field strength of 10 kV / mm was 1260 hours.
[0063] Comparative Example 1
[0064] This comparative example is a commercially available multi-gel powder mica tape without thermal conductive powder filling, and the national standard unified product model is 5440-1 (see GB / T 5019.8-2009 Epoxy Glass Cloth Powder Mica Tape). This comparative example contains a layer of powder mica paper, two layers of glass cloth and epoxy-tungsten resin adhesive, wherein the mass per unit area of each component material is: powder mica paper 85g / ㎡, two layers of alkali-free glass cloth 40g / ㎡ in total, epoxy-tungsten resin adhesive 75g / ㎡, the total mass per unit area is 200g / ㎡, and the thickness of the mica tape is 0.14±0.02mm.
[0065] The multi-gelatin powder mica tape of this comparative example was used to prepare a simulated wire rod sample with a single-side insulation thickness of 3.5 mm by a hot pressing process. According to the test methods specified in relevant national or industry standards, the thermal conductivity of the main insulation was measured to be 0.27 W / (m·K), the breakdown field strength was 34 kV / mm, and the electrical life under a field strength of 10 kV / mm was 1350 h.
[0066] Comparative Example 2
[0067] This comparative example is a high thermal conductivity multi-glue powder mica tape filled with thermal conductive powder. This comparative example contains a layer of powder mica paper, two layers of glass cloth, epoxy-tungsten resin adhesive and BN thermal conductive powder, wherein the mass per unit area of each component material is: powder mica paper 65g / ㎡, two layers of alkali-free glass cloth totaling 40g / ㎡, epoxy-tungsten resin adhesive 85g / ㎡, BN thermal conductive powder 60g / ㎡, the total mass per unit area is 250g / ㎡, and the thickness of the mica tape is 0.18±0.02mm.
[0068] The preparation steps of this comparative example are as follows:
[0069] (1) Adhesive preparation
[0070] Put 35kg of bisphenol A liquid epoxy resin with an epoxy value of 0.44mol / 100g into the reactor, start stirring, heat to 120℃, add 15kg of bisphenol A solid epoxy resin with an epoxy value of 0.12mol / 100g, stir for 1h, add 50kg of tung resin, and stir at 100℃ for 1h. After stopping heating, add 50kg of toluene and 50kg of acetone in turn, continue stirring and cool naturally. When the temperature drops below 40℃, add 0.04kg of curing accelerator, stir for 1h, discharge, filter, and barrel, and an epoxy-tung resin adhesive with a solid content of 50% is obtained.
[0071] (2) Thermally conductive powder and adhesive composite
[0072] 100 kg of the epoxy-tungsten resin adhesive with a solid content of 50% obtained in step (1) is put into a stirring and dispersing tank, and after starting stirring, 35.3 kg of BN thermal conductive powder with a median particle size of 20 μm is added and stirred for 2 hours to obtain an epoxy-tungsten resin adhesive containing thermal conductive powder.
[0073] (3) Gluing of glass cloth
[0074] The epoxy-Tungsten resin adhesive containing thermally conductive powder obtained in step (2) is transferred to the upper and lower glue tanks of the mica tape gluing machine, both of which are equipped with stirring devices, and glue is applied to the upper and lower layers of alkali-free glass cloth with a quantitative amount of 20g / ㎡ respectively. By adjusting the solid content of the adhesive, the speed of the mica tape machine and the rotation speed of the gluing roller, the glue amount is controlled to meet the requirements.
[0075] (4) Lamination, drying, winding and slitting
[0076] The two layers of glass cloth glued in step (3) are compounded with powdered mica paper with a basis weight of 65 g / m2, and then put into a drying oven for drying: the temperature of the front section of the drying oven is controlled at 60-70°C, the temperature of the middle section is controlled at 110-120°C, the temperature of the rear section is controlled at 80-90°C, and the speed is controlled at 1.5-2 m / min. After winding and slitting, the high thermal conductivity multi-glue powdered mica tape of this comparative example without improving the intrinsic thermal conductivity is obtained.
[0077] The high thermal conductivity multi-resin powder mica tape prepared in this comparative example was used to make a simulated wire rod sample with a single-side insulation thickness of 3.5 mm by hot pressing. According to the test method specified in the relevant national or industry standards, the thermal conductivity of the main insulation was measured to be 0.45 W / (m·K), the breakdown field strength was 23 kV / mm, and the electrical life under the field strength of 10 kV / mm was 700 hours. The degradation of the breakdown field strength and electrical life makes it impossible to apply high powder filling products, which is also the reason why the existing technology cannot provide mica tapes with both high thermal conductivity and excellent electrical properties.
[0078] Comparative Example 3
[0079] This comparative example is a high thermal conductivity multi-glue powder mica tape filled with thermal conductive powder, which contains a layer of powder mica paper, two layers of glass cloth, an adhesive and BN thermal conductive powder. The preparation method is the same as that of comparative example 2; the mass per unit area of each component material is: powder mica paper 85g / ㎡, two layers of alkali-free glass cloth totaling 40g / ㎡, adhesive 80g / ㎡, BN thermal conductive powder 30g / ㎡, the total mass per unit area is 235g / ㎡, and the thickness of the mica tape is 0.16±0.02mm; the adhesive is the epoxy-tungsten resin adhesive of comparative example 2.
[0080] The high thermal conductivity multi-resin powder mica tape prepared in this comparative example was used to prepare a simulated wire rod sample with a single-side insulation thickness of 3.5 mm using a hot pressing process. The thermal conductivity of the main insulation was measured to be 0.32 W / (m·K) according to the test method specified in the relevant national or industry standards, and the improvement in thermal conductivity was too small.
[0081] The performance test results of the main insulation obtained in the above embodiments and comparative examples are summarized in Table 1.
[0082]
[0083] It will be easily understood by those skilled in the art that the above-described embodiments are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high thermal conductivity multi-resin powder mica tape, characterized in that: The invention is a composite of mica paper, alkali-free glass cloth, adhesive and inorganic thermal conductive powder, wherein the mass per unit area of each component material is: 60-90g / ㎡ of mica paper, 25-45g / ㎡ of alkali-free glass cloth, 60-90g / ㎡ of adhesive, and 20-40g / ㎡ of inorganic thermal conductive powder; liquid epoxy resin and curing agent are used as raw materials, and reacted in a solvent to obtain the adhesive; the curing agent is 4,4′-dihydroxybiphenyl, 4,4′-diaminobiphenyl, 4,4′-dicarboxylic acid biphenyl, 4,4′-dicarboxylic acid The inorganic thermally conductive powder is one or more of p-terphenyl and 4,4′-dihydroxy-p-terphenyl, or the curing agent is one or more of 4,4′-dihydroxybiphenyl, 4,4′-diaminobiphenyl, 4,4′-dicarboxylic acid biphenyl, 4,4′-dicarboxylic acid p-terphenyl, 4,4′-dihydroxy-p-terphenyl and one or more of resorcinol formaldehyde resin and hydroquinone formaldehyde resin; the median particle size of the inorganic thermally conductive powder is 0.1 to 30 μm; the inorganic thermally conductive powder is one or two of BN and Al2O3.
2. The high thermal conductivity multi-resin powder mica tape according to claim 1, characterized in that: The liquid epoxy resin is one or more of phenolic epoxy resin, resorcinol diglycidyl ether, bisphenol A type liquid epoxy resin, and bisphenol F type liquid epoxy resin.
3. The high thermal conductivity multi-resin powder mica tape according to claim 1, characterized in that: In the high thermal conductivity multi-resin powder mica tape, the alkali-free glass cloth is one layer or two layers; when the alkali-free glass cloth is two layers, the powder mica paper is located between the two layers of alkali-free glass cloth.
4. The method for preparing the high thermal conductivity multi-resin powder mica tape according to claim 1, characterized in that: Liquid epoxy resin and curing agent are used as raw materials, reacted in a solvent to obtain an adhesive, and then thermal conductive powder is added to obtain an adhesive containing thermal conductive powder; then the adhesive containing thermal conductive powder is coated on alkali-free glass cloth, and then compounded with powdered mica paper to obtain the high thermal conductivity multi-glue powdered mica tape.
5. Use of the high thermal conductivity multi-resin powder mica tape according to claim 1 in the preparation of thermal conductive insulating materials.
6. Application of the high thermal conductivity multi-resin powder mica tape according to claim 1 in the preparation of main insulation of high-voltage motors.
Citation Information
Patent Citations
High-heat conducting high-air permeability less-glue mica tape and preparing method thereof
CN102693791A
Nano-enhanced rich resin mica tape with high thermal conductivity and applications thereof
CN103400665A
Mica tape with high heat conductivity coefficient and preparation method thereof
CN114664501A
Coil for electric rotating machine, and mica tape and mica sheet used for the coil insulation
US20040094325A1
High-thermal-conductivity insulating layer material, metal substrate, and preparation method
WO2021128895A1
